Numerical comparison of premixed H2/air combustion characteristic of three types of micro cavity-combustors with guide vanes, bluff body, guide vanes and bluff body respectively. (9th July 2021) - Gao, Wei; Yan, Yunfei; Huang, Lujing; Shen, Kaiming; He, Ziqiang; Gao, Bo
Abstract: Micro-scale combustion is facing the problems of ignition difficulty, combustion instability, and low combustion efficiency. Therefore, it is necessary to improve the combustion characteristics in micro-combustor to expand the application range of micro-combustor. Focusing on the problem of the weak preheating effect of the micro cavity-combustor, the guide vanes are constructed to enhance the combustion near the cavity, and further combine with the bluff body to enhance combustion. The combustion characteristics of three types of cavity combustors with guide vanes (CCGV), bluff body (CCBB), bluff body, and guide vanes (CCGB) respectively are compared and analyzed under different inlet velocities (8–32 m/s), equivalence ratios (0.6–1.4), and wall materials (quartz glass, steel, and SiC). Results show that the guide vanes can greatly improve the combustion intensity near the cavity and improve the combustion stability of the cavity combustor. The combustion efficiency of CCGV and CCGB are increased by 43.04% and 85.96% respectively than CCBB when the inlet velocity is 32 m/s. The reaction heat of CCGV is 244.5 W when inlet velocity is 32 m/s, which is 0.55 times and 1.57 times that of CCGV and CCBB, respectively. The temperature uniformity and mean temperature of the outer wall of CCGV and CCGB both are better than that of CCGB. The combustion efficiency of CCGB is the highest among three combustors under the same equivalence ratio, especially when the equivalence ratio is less than 1. The reaction intensity in the cavity of the CCGV and CCGB with steel wall material is highest than that of the combustor with the other two wall materials. Wall materials with high thermal conductivity have a better preheating effect. Compared with quartz as the wall material, the mean temperature of the external wall of CCGV and CCGB using steel and silicon carbide as the wall material both increase by more than 130 K, and the wall heat loss both increase by more than 50%. Highlights: The combustion characteristics of three types of cavity combustors are compared. The guide vanes can greatly improve the combustion intensity near the cavity and improve the combustion stability. The reaction heat of CCGB is 0.55 times and 1.57 times that of CCGV and CCBB respectively when inlet velocity is 32 m/s. The combustion state in CCGB is the best among three combustors under the same equivalence ratio.